Bacterial Detection and Differentiation via Direct Volatile Organic Compound Sensing with Surface Enhanced Raman Spectroscopy. Issue 27 (21st September 2017) - DeJong, Caitlin S.; Wang, David I.; Polyakov, Aleksandr; Rogacs, Anita; Simske, Steven J.; Shkolnikov, Viktor
Abstract: Current methods for detecting bacterial infections, such as culture and morphological analysis of bacterial colonies, are time and labor intensive. Through the direct detection of bacterial volatile organic compounds (VOCs), via surface enhanced Raman spectroscopy (SERS), we report here a reconfigurable assay for the identification and monitoring of bacteria. We demonstrate differentiation between highly clinically relevant organisms: Escherichia coli, Enterobacter cloacae, and Serratia marcescens . This is the first differentiation of bacteria via SERS of bacterial VOC signatures. The assay also detected as few as 10 CFU/ml of E. coli in under 12 hrs, and detected E. coli from whole human blood and human urine in 16 hrs at clinically relevant concentrations of 10 3 CFU/ml and 10 4 CFU/ml, respectively. In addition, the recent emergence of portable Raman spectrometers uniquely allows SERS to bring VOC detection to point‐of‐care settings for diagnosing bacterial infections. Abstract : We report here a reconfigurable assay for the identification and monitoring of bacteria through direct detection of bacterial volatile organic compounds (VOCs) via surface enhanced Raman spectroscopy (SERS). We demonstrate differentiation between highly clinically relevant organisms: Escherichia coli, Enterobacter cloacae, and Serratia marcescens and detection of as few as 10 CFU/ml of E. coli in under 12 hrs from culture, and of 10 3 CFU/ml and 10 4 CFU/ml from whole human blood and human urine in 16 hrs.